ANALISIS PEMANFAATAN PERPUSTAKAAN RAMAH ANAK DAN KETERSEDIAAN BAHAN BACAAN TERHADAP PENGEMBANGAN LITERASI MEMBACA SISWA KELAS III SEKOLAH DASAR - Tsaqifah, Ainun; Widiawati; Yayu Andika Amin; Tarman A. Arif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading literacy is a fundamental competence that elementary school students need to acquire as a foundation for understanding information and supporting academic achievement. One of the efforts to develop students’ reading literacy is through the implementation of child-friendly libraries and the availability of appropriate reading materials. This study aims to analyze the utilization of a child-friendly library and the availability of reading materials in developing reading literacy among third-grade elementary school students at UPT SPF SD Inpres Mariso 1. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of the principal, library manager, third-grade teacher, and 30 students of class III B. Data were collected through observation, in-depth interviews, and documentation. The data were analyzed using the Miles, Huberman, and Saldaña interactive model, including data condensation, data display, and conclusion drawing and verification. The results showed that the Tunas Bangsa Library has implemented child-friendly library characteristics through a comfortable learning environment, diverse reading collections, and literacy programs integrated into learning activities. The availability of varied reading materials contributed to increased students’ reading interest, library visits, reading habits, and reading comprehension skills. However, several challenges were identified, including differences in students’ reading abilities and the limited availability of some popular book collections. This study concludes that child-friendly libraries supported by adequate reading materials play an important role in strengthening reading literacy development among elementary school students.